Design and Implementation of NodeMCU ESP8266-Based Smart Home System as Residential Energy Efficiency Solution - Aziza, Miladina Rizka; Widyanto, Hafidin Bangun; Dwiputra, Febrian Daniel; Cahayanti, Putri Nur; Prawimuliasta, Enggar Kabisafira; Nugroho, Rizky Wahyu (Institut Riset dan Publikasi Indonesia, 2026)
The household sector accounts for approximately 42.41% of Indonesia's total electricity consumption (122,339.69 GWh in 2023), making it a strategic priority for energy efficiency efforts aligned with the Sustainable Development Goals (SDGs), particularly SDG 7, SDG 9, SDG 11, and SDG 13. This study presents the design of a NodeMCU ESP8266-based smart home system integrated with the ThingSpeak platform and an Android application built with MIT App Inventor. This system is capable of integrating three main functions, including controlling and monitoring room lights using an LDR sensor, controlling the AC along with monitoring temperature and humidity using a DHT11 sensor, and monitoring water levels using an HC-SR04 ultrasonic sensor within a single low-cost NodeMCU platform. System performance was evaluated through functional testing of each subsystem using calibrated reference instruments, with accuracy calculated by comparing measured values against theoretical reference values. The DHT11 sensor achieved 95.62% accuracy for temperature and 98.15% for humidity, while the HC-SR04 sensor achieved 97.06% accuracy. With a total component cost below IDR 1.5 million, this system demonstrates that a multi-subsystem smart home solution can be implemented affordably using locally available components, supporting residential energy efficiency and the SDGs 2030 agenda.